Autophagy and Aging: Roles in Skeletal Muscle, Eye, Brain and Hepatic Tissue - Li, Ping; Ma, Yuanzheng; Yu, Chengwei; Wu, Shoutong; Wang, Kai; Yi, Hongyang; Liang, Weizheng (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an evolutionarily conserved process that promotes cell to disassemble unnecessary or dysfunctional structures, thereby maintaining cellular homeostasis and renewal of organelles. Aging is a universal phenomenon characterized by the progressive accumulation of impaired molecular and reduced turnover of cellular components. Recent evidence suggests a unique role for autophagy in aging and age-related disease. Indeed, autophagic activity declines with age and enhanced autophagy may prevent the progression of many age-related diseases and prolong life span. All tissues experience changes during aging, while the role of autophagy in different tissues varies. This review summarizes the links between autophagy and aging in the whole organism and discusses the physiological and pathological roles of autophagy in the aging process in tissues such as skeletal muscle, eye, brain and liver.